Transformation of press regulation: a critical analysis of the 2013 changes at the Press Council of South Africa - Sharra, Albert Edwin (My University, 2018)
This study used qualitative research design comprising of document analysis and in-depth interviews with system users to understand the changes that converted Press Council of South Africa (PCSA) from a self-regulatory body of media practice and ethics to Independent Co regulation in 2013, following a recommendation by the Press Freedom Commission (PFC). Further, it analyses whether and in what ways the changes have met the key aims of Independent Co-regulation as set out by the PFC. Since standards of how the press should operate grow out of ideas and expectations of the media in a society; this study used the normative theories of the press to give a theoretical perspective that the effectiveness of a regulatory mechanism, determines its credibility and future. Findings indicate that the 2013 changes at the Council have transformed the regulatory system for the better by giving it sharper teeth to deal with publications that breach the code, promoting media professionalism to meet the normative expectations of the society, improving the system’s accessibility and giving the non-industry a bigger voice in the system. However, despite the general improvement, there are still some few weaknesses that need to be addressed to avoid possible criticism towards the system
A research report submitted in partial fulfilment for the degree of Master of Arts in Journalism and Media Studies to the Faculty of Humanities at the University of the Witwatersrand, Johannesburg, 2018